Knowledge management in social work: The interplay of knowledge sharing platforms. (March 2014) - Leung, Zeno CS
This article discusses the research on a social service organization practising knowledge management in Hong Kong. Discussion on different knowledge sharing activities conducted on different platforms and their interplay illustrates that a good balance between the two knowledge management approaches can better achieve the objectives in this newly developed management area.